Knotworking in an emergency response team: understanding team communication and process - Janet W. Colvin (Qualitative Research in Medicine & Healthcare)
Over the last 30 years, many studies have focused on responses to crisis in organizations. Crises can occur at any time of the day or night on a regular but unforeseen basis and are characterized by high consequences and short decision time. In healthcare, multidisciplinary crisis management or rapid response teams (RRT) have become more common. RRTs allow for a cross-sectional focus on patients’ needs and, thereby, prevent avoidable deaths or significant harm. This study uses Activity Theory and knotworking theory to examine how communication, multiple roles and power structures are negotiated in RRT’s in a large intermountain teaching hospital. Results from focus groups indicate a single-minded focus on training for system errors may miss important aspects. Knotworking theory is promising because it helps providers move beyond an understanding of teamwork to an understanding of how objectives can be shared and merged.